Respuesta :

znk

Answer:

x = 2; y = -9  

Step-by-step explanation:

(1)    4x  + 6y = -46

(2) -2x  – 2y =   14     Multiply (2) by 2

(3)  -4x  - 4y =   28     Add (1) and (3)

              2y =  -18      Divide each side by 2

                y =   -9     Substitute into (2)

-2x – 2(-9) =   14

    -2x + 18 =   14     Subtract 18 from each side

           -2x =    -4     Divide each side by -2

              x =     2

=====

Check:

(1)    4×2 + 6(-9) = -46

             8 – 54 = -46

                  -46 = -46

(2) -2×2 – 2(-9) = 14

             -4 + 18 = 14

                    14 = 14